Maternity healthcare providers' self-perceptions of well-being during COVID-19: A survey in Tshwane Health District, South Africa - Sarie Oosthuizen; Anne-Marie Bergh; Antonella Silver; Refilwe Malatji; Vivian Mfolo; Tanita Botha (AOSIS, 2022)
Background: Mental health manifestations such as depression and anxiety disorders became more marked during the coronavirus disease 2019 (COVID-19) pandemic as frontline healthcare workers struggled to maintain high-quality intrapartum care and essential health services. Aim: This study aimed to identify maternity healthcare providers' self-perceptions of changes in their feelings of mental well-being. Setting: Ten midwife obstetric units and the labour wards of four district hospitals in Tshwane Health District, South Africa. Methods: We conducted an anonymous, cross-sectional survey amongst a convenience sample of 114 maternity healthcare workers to gauge the changes in healthcare workers' experience and perceptions of well-being during the COVID-19 pandemic. Four items measured the perceived changes on a scale of 0-10 for the periods before and during COVID-19, respectively, namely feelings of fear or anxiety, stress, depression and anger. Results: The majority of participants were professional nurses (37%) and advanced midwives (47%). They reported a significant change in well-being from before the pandemic to during the pandemic with regard to all four items (p 0.0001). The biggest 'before-during' difference was in perceptions of fear or anxiety and the smallest difference was in perceptions of anger. A framework was constructed from the open-ended responses to explain healthcare workers' understanding and perceptions of increased negative feelings regarding their mental well-being. Conclusion: The observed trends in the changes in healthcare workers' self-perceptions of their mental well-being highlight the need for further planning to build resilient frontline healthcare workers and provide them with ongoing mental health support and improved communication pathways.